Multiple TGF-? Superfamily Signals Modulate the Adult Drosophila Immune Response. - Clark, R.I.; Woodcock, K.J.; Geissmann, F.; Trouillet, C.; Dionne, M.S. (Current Biology, 2011)
TGF-? superfamily signals play complex roles in regulation of tissue repair and inflammation in mammals [1]. Drosophila melanogaster is a well-established model for the study of innate immune function [2, 3] and wound healing [4-7]. Here, we explore the role and regulation of two TGF-? superfamily members, dawdle and decapentaplegic (dpp), in response to wounding and infection in adult Drosophila. We find that both TGF-? signals exhibit complex regulation in response to wounding and infection, each is expressed in a subset of phagocytes, and each inhibits a specific arm of the immune response. dpp is rapidly activated by wounds and represses the production of antimicrobial peptides; flies lacking dpp function display persistent, strong antimicrobial peptide expression after even a small wound. dawdle, in contrast, is activated by Gram-positive bacterial infection but repressed by Gram-negative infection or wounding; its role is to limit infection-induced melanization. Flies lacking dawdle function exhibit melanization even when uninfected. Together, these data imply a model in which the bone morphogenetic protein (BMP) dpp is an important inhibitor of inflammation following sterile injury whereas the activin-like dawdle determines the nature of the induced immune response.